Multilevel factors affecting mental health literacy among older adults: a qualitative study based on social ecological model - Wang, Yan; Jia, Shoumei; Wang, Anni; Li, Huiyuan; Xu, Rongjing; He, Xuyan (Frontiers in Public Health, 2025)
BackgroundMental health challenges among older adults are a growing global health priority. Mental health literacy (MHL) is a critical factor in mitigating these challenges and enhancing mental well-being. However, MHL levels among older adults remain relatively low, and its multilevel determinants are poorly characterized.ObjectivesThis study aimed to explore the multilevel factors influencing MHL among older adults from a dual perspective encompassing both older adults and geriatric healthcare providers, using a social ecological model (SEM).MethodsA qualitative descriptive study design was used. Semi-structured interviews were conducted with 15 older adults and 12 geriatric healthcare providers (doctors and nurses) in Shanghai between October 2024 and January 2025. Directed content analysis was guided by the SEM. The data were analyzed using NVivo 14.0.ResultsFour SEM-aligned themes emerged as factors influencing MHL: (1) individual factors (digital health information acquisition capacity, psychological resilience, experiences with mental illness, and the perceived utility of engaging in mental health promotion activities and seeking professional assistance); (2) interpersonal factors (peer interactions and family functioning); (3) community factors (the intensity and modality diversity of mental health promotion activities, availability of mental health resources within healthcare institutions, and the sanitary conditions of residential environments); (4) societal factors (stigmatization of mental illness, privacy norms, as well as healthcare delivery systems and health insurance schemes).ConclusionUsing the SEM, this study explored the complex and multilevel factors that may influence older adults’ MHL. Older adults’ MHL is influenced by a combination of individual, interpersonal, community, and societal factors. Future studies should integrate culturally adaptive frameworks with policy-driven strategies to develop multilevel interventions encompassing interpersonal support systems, community resource coordination, and structural destigmatization programs for older populations.